Zonas cardinales y orientación entre los qomléʔk (tobas del oeste de Formosa, Argentina) - María Belén Carpio; Cecilia Paula Gómez (Journal de la Société des Américanistes)
This paper analyzes the different ways in which the Tobas of Western Formosa, Qomléʔk, also known as Tobas de Sombrero Negro, refer to cardinal zones and their contexts of use. We suggest that definitions describing and naming these areas are bodily experienced and are linked to the winds, the course of the sun, and the Pilcomayo River, with differences between people of different generations. We also describe how some of the lexemes that encode cardinal zones are used to encode position/orientation between entities not only in a geographic (large-scale) space, but also in a manipulable one (e.g. objects located on a table). We propose, as a hypothesis, that the lexeme cháʔhema “up there (South)” may refer to the “south celestial pole,” identifiable by the Tobas’ use of certain asterisms.